Higher strength gain after hypoxic vs normoxic resistance training despite no changes in muscle thickness and fractional protein synthetic rate. Issue 8 (29th July 2021) - van Doorslaer de ten Ryen, Sophie; Warnier, Geoffrey; Gnimassou, Olouyomi; Belhaj, Mehdi R.; Benoit, Nicolas; Naslain, Damien; Brook, Matthew S.; Smith, Kenneth; Wilkinson, Daniel J.; Nielens, Henri; Atherton, Philip J.; Francaux, Marc; et al.
Abstract: Acute hypoxia has previously been suggested to potentiate resistance training‐induced hypertrophy by activating satellite cell‐dependent myogenesis rather than an improvement in protein balance in human. Here, we tested this hypothesis after a 4‐week hypoxic vs normoxic resistance training protocol. For that purpose, 19 physically active male subjects were recruited to perform 6 sets of 10 repetitions of a one‐leg knee extension exercise at 80% 1‐RM 3 times/week for 4 weeks in normoxia (FiO2 : 0.21; n = 9) or in hypoxia (FiO2 : 0.135, n = 10). Blood and skeletal muscle samples were taken before and after the training period. Muscle fractional protein synthetic rate was measured over the whole period by deuterium incorporation into the protein pool and muscle thickness by ultrasound. At the end of the training protocol, the strength gain was higher in the hypoxic vs the normoxic group despite no changes in muscle thickness and in the fractional protein synthetic rate. Only early myogenesis, as assessed by higher MyoD and Myf5 mRNA levels, appeared to be enhanced by hypoxia compared to normoxia. No effects were found on myosin heavy chain expression, markers of oxidative metabolism and lactate transport in the skeletal muscle. Though the present study failed to unravel clearly the mechanisms by which hypoxic resistance training is particularly potent to increase muscle strength, it is important message to keep in mind that this training strategy could be effective for all athletes looking at developing and optimizing their maximal muscle strength.